Evaluating employability in contexts of change: validation of a scale - González-Navarro, Pilar; Córdoba-Iñesta, Ana Isabel; Casino-García, Ana María; Llinares-Insa, Lucía Inmaculada (Frontiers in Psychology, 2023)
Introduction Employability is a crucial factor in managing to emerge and changing job demands. This study validates an expanded version of the Employability Appraisal Scale: EAS-60, as an instrument to identify and improve competencies for employability. Method The EAS-60 was tested in a cross-sectional study in a Spanish population. An exploratory study was carried out using a sample of 188 workers, and the scale’s structure was analyzed and confirmed in two Confirmatory Factor Analyses using a sample of 527 workers. Finally, reliability and validity were evaluated. Results Exploratory and confirmatory analyses provide evidence supporting the multi-dimensional structure. The scale presents good psychometric properties and criteria for interpreting the scores. Discussion The EAS-60 is a reliable and valid instrument. It allows Human Resource Managers to offer career plans at work that include specific actions of job socialization, training, improvement of specific skills, etc. Furthermore, employees can increase their employability and develop their professional careers.